Tre sculture del Rinascimento Recuperi e restauri a Villa La Quiete - GIOMETTI, Cristiano; PEGAZZANO, DONATELLA (Cataloghi e collezioni, 2019)
The exhibition at Villa La Quiete focuses on three important Renaissance sculptures, which had never been exposed to the public before. On this occasion, the works were carefully restored, continuing on the path of the previous restauration of the Villa's artistic heritage at the hands of the University of Florence; the new restoration was supported by the Terna group, whose liberal donation helped restore one of the works on display, namely the beautiful in stucco Madonna with Child from Lorenzo Ghiberti's workshop. This work comes with a rare terracotta piece of a Madonna with Child, by one of Donatello's followers, and a Christ, the Saviour, in painted terracotta as well, made by the artist Agnolo di Polo, who trained in Andrea Verrocchio's workshop. The three sculptures are a part of the oldest core of the Villa's collections, and represent a relevant example of the refined production of the multifaceted workshops of the Renaissance in Florence.